Alkali Activation of Coal Fly Ash: Characterization and Potential for Oil Remediation - Ayu Fahimah Diniyah Wathi; Aisyiah Restutiningsih Putri Utami; Teguh Pambudi; Meiyanti Ratna Kumalasari; M. Sulthon Nurharman Syah Putra; Sri Setyaningsih; Dola Suciana (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
Fly ash, a byproduct of coal combustion, has attracted increasing attention as a low-cost adsorbent for environmental remediation. This study aims to investigate the effect of alkali activation on the structural and surface characteristics of fly ash and to evaluate its potential for oil remediation. In this work, fly ash was activated using sodium hydroxide (NaOH) followed by thermal treatment at 250 C. The structural and surface properties of the materials before and after activation were characterized using Fourier Transform Infrared spectroscopy (FTIR), X-ray Diffraction (XRD), and Brunauer–Emmett–Teller (BET) surface area analysis. FTIR analysis indicated changes in the surface functional groups of fly ash after alkali activation, while hydrocarbon-related bands observed after contact with used oil suggested the presence of oil-derived compounds on the adsorbent surface. XRD results showed that the activated fly ash retained a predominantly amorphous phase with slight changes in crystallinity. BET analysis revealed only a slight increase in specific surface area from 22.71 to 23.53 m2g-1, accompanied by a small increase in average pore diameter from 5.49 to 5.77 nm, indicating limited modification of the mesoporous structure after alkali activation. These structural modifications suggest that alkali activation alters the surface characteristics of fly ash and may support its potential use in oil remediation. The findings indicate that alkali-activated fly ash has potential as an economical and sustainable adsorbent for environmental remediation applications, particularly for the treatment of oil-contaminated waste.Keywords: alkaline activation, adsorbent, BET, FTIR, XRD